Risk assessment of three sheep stocking modes via identification of bacterial genomes carrying antibiotic resistance genes and virulence factor genes. (1st December 2022) - Yuan, Bo; Ma, Yanwen; Ren, Jingyao; Ding, Guochun; Zhou, Ningcong; Liang, Jinsong; Sun, Ying
Abstract: In order to protect the prairie ecological environment, intensive farming has become a prevalent method of sheep stocking. However, the link between captivity stocking mode and ecological risk of sheep feces is still poorly understood. In this study, metagenomics was used to identify the environmental risk of sheep feces among three stocking modes. Our results showed that captivity mode (C) elevated antibiotic resistance in feces, with the abundance of antibiotic resistance genes (ARGs) (5.381 copies/cell) higher than that of half-pen stocking (Fh) (1.093 copies/cell) and grazing mode (Fr) (0.315 copies/cell) (Duncan's test, P < 0.05). Virulence factor genes (VFGs) analysis showed offensive virulence factors had the highest abundance in captivity feces (C: 3.826 copies/cell, Fh: 0.342 copies/cell, Fr: 0.163 copies/cell) (Duncan's test, P < 0.05). 15 metagenome-assembled genomes (MAGs) were identified as potential pathogenic antibiotic resistant bacteria (PARB) and revealed that Escherichia, Klebsiella may be the main host of ARGs and VFGs in sheep feces. Furthermore, the minimal inhibition concentrations (MIC) of tetracycline of E. coli in the captivity feces was 8.6 times and 4.7 times than that of grazing and half-pen stocking samples, respectively. The Non-metric multidimensional scaling (NMDS) revealed that high stocking density leads to feces causing increased harm to the environment. Although feces from sheep raised in captivity and half-pen stocking modes are easier to collect, they are more harmful to the environment and aerobic composting should be done before their application to farmland. This work provides a guideline for better control of the environmental risk of sheep feces from different stocking modes. Graphical abstract: Image 1 Highlights: Escherichia, Corynebacterium and Bacillus were the dominant genera in sheep feces. Offensive virulence factors had the highest abundance in sheep feces. 955 MAGs were recovered and 15 MAGs were identified as potential PARB. Escherichia and Klebsiella were the main host of ARGs and VFGs in feces using MAG. Sheep feces under captivity mode may be more harmful to the environment.